Ecological effects of land use and land cover changes on lakes in urban environments - Krishnan, Ganga; Shanthi Priya, Radhakrishnan; Senthil, Ramalingam (Sustainable development (Bradford, West Yorkshire, England), 2024)
Urban lakes confront significant threats due to changes in land use and land cover (LULC) resulting from urbanization and subsequent climate change. This review discusses the intricate effects of the urban heat island phenomenon on lakes, specifically attributed to LULC changes. Utilizing the Scopus and Web of Science databases, this study gathers the most pertinent earlier research in the LULC and water bodies. This study systematically categorizes variables into five distinct groups and scrutinizes the drivers, parameters, tools, and management strategies influencing the LULC dynamics on lakes. A research gap is identified in understanding the conjoined impacts of LULC and urban heat island effects within urban lake environments. The review further investigates diverse ways in which LULC impacts lakes, intersecting with multiple United Nations sustainable development goals (SDGs), notably SDGs 6, 11, 13, and 15. Consequently, this review serves as a valuable contribution to the understanding of LULC to provide substantial benefits to the urban climate research toward meeting SDGs.